Efeitos da inovação e dos investimentos em meio embiente no desempenho de empresas brasileiras e espanholas - Farias, Ivaneide Ferreira (2018)
The globalized scenario requires companies to conduct business that prioritize market development, profitability increase, continuity of operations, and adaptation to changes and demands of society. In this context, in the light of the Resource-Based View (RBV) and Legitimacy Theories, innovation and environmental investments constitute antecedents of gaining competitive advantages and legitimacy. Despite the extensive number of studies on these themes, the results are divergent and rarely address the alignment of strategies to innovate and invest in environmentally sustainable practices in organizations located in different economic realities. In this perspective, the present research aims to analyze the influence of innovation and environmental investments on the performance of companies from different economic contexts – Brazilian and Spanish. The quantitative descriptive research used documentary procedure and statistical techniques, such as mean tests, multiple correspondence analysis, and multiple linear regression. The sample comprises Brazilian and Spanish public companies that disclosed environmental and innovation information from 2011 to 2016. The main sources of data surveyed were the Global Reporting Initiative (GRI) sustainability reporting standards, the annual reports, the standard financial statements, the Economática® and Amadeus – Bureau van Dijk databases. Among the research results, it was observed that P&D investments, number of patents, and environmental investments are significantly higher in Spanish companies. It was identified the positive effect of innovation (R&D and patents) on the Tobin’s Q of Brazilian companies, and regarding the Spanish companies, a positive influence was observed only on patents in the Tobin’s Q. It was verified that the environmental investments of Brazilian companies positively influenced their performance (Tobin’s Q and EBITDA); as for the Spanish companies, only the effects of these investments on the Tobin’s Q were shown. The analysis of the effects of innovation on environmental investments revealed the influence of P&D and patents on the environmental expenditures of Brazilian companies and on the general sample, while among Spanish companies only the positive impact of patents can be verified. It can be concluded that the differences identified between the Brazilian and Spanish companies can find support in the economic and legal contexts in which they are inserted and in the conversion time of each strategy into competitive advantages.